Solving microgrid economic dispatch with renewable energy using differential evolution immunized ant colony optimization technique (Deiant) - Rahil Hanim binti Ghazali (2023)
Nowadays, due to increasing industrial development and number of population, the electrical power demand has been increasing rapidly. Hence electrical power utilities need to make sure the electrical power neccessity is fulfilled. Unfortunately, by the increasing electrical power demand the non-renewable energy source such as fossil fuel, has been decreasing rapidly.